07 Simultaneous Positron Emission Tomography and Magnetic Resonance Imaging of Receptors Using a Novel Combined Pre-Clinical Micropet/Mr System. (20th November 2012) - Bird, JLE; Hawkes, RC; Manavaki, R; Sawiak, SJ; Williamson, DJ; Aigbirhio, FI; Rudd, JHF; Bennett, M; Gillard, JH; Carpenter, TA; Warburton, EA; Davenport, AP
Abstract : Vascular and cardiac diseases are complex pathologies and preclinical models are required to fully investigate the multifactorial interactions. In vivo imaging techniques are important research tools in quantifying pathogenic mechanisms and positron emission tomography (PET) is an imaging modality which has the chemical specificity and the sensitivity to quantify biological processes in vivo. However, PET tracer uptake does not usually provide sufficiently detailed anatomical structure to accurately allocate receptor activity to precise tissue regions. This may be overcome by simultaneous imaging with magnetic resonance imaging (MRI). The aim of the study was to evaluate the combined PET/MRI scanner for the investigation of biological processes in rodents. N-(5-fluoro-2-phenoxyphenyl)-N-(2-[18F]-fluoroethyloxy-5-methoxybenzyl)acetamide ([18F]FEDAA1106) binds the translocator protein (TSPO) which is up-regulated in activated macrophages and may quantify vascular inflammatory pathologies. Dynamic in vivo imaging was carried out using a modified Focus F120 microPET incorporated into a bespoke 1 Tesla MR magnet (1). The pharmacokinetic profile of [18F]-FEDAA was characterised in mice. Simultaneously acquired PET and MRI reconstructed images were aligned together and the combined images revealed rapid uptake of [18F]-FEDAA into the heart, liver, lungs, kidneys and brain. Time activity curves were constructed using regions of interest delineated by the MR images and showed the expected pharmacokinetic profile. Thus, the results show that the fused anatomical-functional image not only provides anatomical context to the PET data, but can also allow improved quantification by more accurately defining the region of radioactive emission. (1) Hawkes RC, et al. Technol Cancer Res Treat. 2010; 9(1):53–60.